Aspek Fisika dalam Perancangan Pesawat Aeromodeling Jenis Delta Wing - Muhammad Zuhdi Ronodirdjo; Muh Makhrus; Wahyudi Wahyudi (Kappa Journal, 2021)
The Delta Wing aeromodeling aircraft uses a symmetrical airfoil where the top of the wing is the same as the bottom. The main aspects in the design of the Delta Wing aircraft are center of gravity, the engine thrust, the air resistance, the lift and the weight. Delta Wing aircraft are dominated by jet-engined aircraft with the advantages of high speed and small air resistance. From the design and field trials, it was concluded that the minimum thrust of the Delta Win aircraft must be equal to 2 times the total weight of the aircraft so that the aircraft is able to maneuver vertically, perform looping maneuvers, roll maneuvers and hovering.